Pembelajaran Kitabah Bahasa Arab Melalui Media Digital Interaktif Berbasis Kaligrafi Dalam Perspektif Teoretis - Lulu Mauludiah; Pradi Khusufi Syamsu; Wawan Arwani (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
Learning Arabic writing skills (kitabah) often faces obstacles. These include low motivation and learners' visual accuracy in complex letter structures. This study aims to theoretically examine how interactive digital media grounded in calligraphy can modernize kitabah learning within the digital education landscape. The research method is library research. It analyzes 15 core journals and supporting literature published between 2021 and 2025. The analysis uses the Technological, Pedagogical, and Content Knowledge (TPACK) framework. This framework examines the synergy among digital technology, pedagogical strategies, and calligraphic content. The results indicate that calligraphy-based interactive digital media can transform kitabah learning. It enables real-time feedback, stroke-order simulation, and fine-motor strengthening. These provide a more precise experience than conventional methods. The theoretical implications emphasize that effective kitabah learning in the digital era needs balanced technology integration. This must occur without reducing the established aesthetic rules of khath. This study offers a strategic roadmap for educators to adopt TPACK-based innovations in Arabic language classrooms.